Challenges in the Use of Personal Protective Equipment among Emergency Nurses in Burkina Faso - Nana, Félicité Wendin-manegdé; Compaore, Mariguetou; So, Abdoulaye; Sanon, Sandrine; Poda, Gislain Gnimbar; Rouamba, Bertrand Guy; Drabo, Drabo Koine (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2025)
Introduction: Healthcare-associated infections (HAIs) are a significant risk in emergency departments. The use of personal protective equipment (PPE) is essential to mitigate these risks, but factors influencing PPE use need further exploration. This study aimed to assess factors affecting PPE use among emergency nurses at Yalgado Ouedraogo University Hospital (CHUYO), Burkina Faso.Methods: A cross-sectional study, with a mixed method of quantitative and qualitative was conducted at Yalgado Ouedraogo University Hospital (CHUYO), Burkina Faso. Study participants were all of the nurses (25 nurses) and resource persons at Emergency Department. Data were collected through interviews using structured questionnaires for the quantitative data and in depth interviews and observations for qualitative data. Data analysis were done descriptively for quantitative data and content analysis and for qualitative data. Qualitative data then were categorized into themes.Results: Most of the participants (95.65%) acknowledged the importance of PPE. The challenge of PPE use were the insufficient availability, poor quality, inadequate training, no room for donning and doffing, no functional laundry service for cleaning reusable PPE, and supply issues. More than 75% of nurses worked without PPE due to stockouts. Hand hygiene compliance was notably low at just 23.33%.Conclusion: PPE's importance has been recognized by the emergency care nurses, however the challenges like insufficient and low quality stock and and infrastructure hinder its effective use. Improving management and training is crucial for enhancing PPE compliance and safety.